Strengthening Restorative Justice in Criminal Justice System Reform: A Comparative Study of Indonesia and the Netherlands - Mohammed Abdu Rehany (ILAW, 2026)
This study analyzes the strengthening of restorative justice in criminal justice system reform through a comparative study between Indonesia and the Netherlands. The research aims to examine how restorative justice is implemented in both countries and how it contributes to the transformation of criminal justice systems toward more humanistic and rehabilitative approaches. A normative legal research method is used with conceptual, statutory, and comparative approaches based on secondary data from legal literature, official documents, and academic publications. The findings show that restorative justice in Indonesia is in a developing stage, primarily implemented through discretionary law enforcement practices, while in the Netherlands it is more institutionalized and integrated into the formal criminal justice system. Both countries share similar objectives in promoting reconciliation, reducing recidivism, and improving justice efficiency. However, differences exist in legal structure, institutional support, and implementation consistency. The study concludes that restorative justice is an important model for criminal justice reform, but its effectiveness depends on legal institutionalization, cultural acceptance, and continuous policy development.